Experiência, formação humana e educação: a dialética negativa como potência do pensamento não idêntico - Cezário, Maria Angélica (2021)
This research seeks to identify possible relationships between the concepts of experience, human formation and education, based on the negative dialectic program, that values the thinking not identical. The main work addressed in this investigation is Negative Dialectic, by Theodor Adorno (2009), also has an interlocution with other works by the same author. The importance of the relationship between the concepts mentioned is due to: the potential that Adornian critic has when analyzes programs that produce positive theoretical concepts; limited freedom and autonomy of people to a damaged society; systematic mechanisms of domination and integration; exploration between men and exaggerated self-preservation. This has brought results for the life of people and for the culture, submitting, in the first case, subjects to a process of de-humanization. Second, culture and its potential of unleashing critical reflections on reality were precarious. That is why cultural training of people, in a damaged society, does not give them intellectual resources to question what, for instrumental reason, was installed. In this way, the people were stimulated to submerge themselves in the social laws, also finding themselves in a state of heteronomy. The thought, due to this heteronomy, had its potential of criticism exercise, resistance and opposition atrophied, which has a great limitation on people that seek to put away of these conditions. Because of that, it is conceived that the negative dialectic program is able a critical interpretation on this result when it creates opportunities to training by the critical intellectual experience, based on differentiality. These, linked to education, can offer important reflections to create favorable contexts to critically analyze the processes whose results have been ruined, questioning the conscience cultivated from the ideals of the administered world and revealing the contradictions of reality. It can, finally, open up to a creatively utopian dimension, being, therefore, a force for mobilizing actions that will be able to create opportunities for transformations.